Transgraniczne sprawy rodzinne w relacjach polsko-brytyjskich w obliczu brexitu - Juryk, Anna (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The purpose of the article is above all to show possible changes in the field of cross-border family matters as a result of Brexit. From a Polish perspective, this topic is particularly socially significant due to the numerous labor migration of Poles to the UK. It is estimated that around one million Poles live in the UK. First, the article presents current sources of law regarding cross-border family matters (EU law, international agreements, internal law). Next, possible solutions to family matters and their strengths and weaknesses were discussed after Brexit. Finally, solutions currently adopted in the UK and the biggest concerns related to them are shown.